Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Connect with professionals ready to provide precise answers to your questions on our comprehensive Q&A platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

Evaluate the expression:

[tex]\[
\tan \frac{7 \pi}{12}
\][/tex]


Sagot :

To find the value of [tex]\(\tan \frac{7 \pi}{12}\)[/tex], let's break down the problem using trigonometric identities, specifically the angle sum identity for tangent. The angle sum identity for tangent is given by:

[tex]\[ \tan(A + B) = \frac{\tan A + \tan B}{1 - \tan A \tan B} \][/tex]

We need to express [tex]\(\frac{7 \pi}{12}\)[/tex] in a form that is more manageable. Notice that:

[tex]\[ \frac{7 \pi}{12} = \frac{3 \pi}{12} + \frac{4 \pi}{12} = \frac{\pi}{4} + \frac{\pi}{6} \][/tex]

So, set [tex]\( A = \frac{\pi}{4} \)[/tex] and [tex]\( B = \frac{\pi}{6} \)[/tex].

Next, we use the known values:
[tex]\[ \tan \left( \frac{\pi}{4} \right) = 1 \][/tex]
[tex]\[ \tan \left( \frac{\pi}{6} \right) = \frac{1}{\sqrt{3}} \][/tex]

Using the angle sum identity:
[tex]\[ \tan \left( \frac{7 \pi}{12} \right) = \tan \left( \frac{\pi}{4} + \frac{\pi}{6} \right) = \frac{\tan \left( \frac{\pi}{4} \right) + \tan \left( \frac{\pi}{6} \right)}{1 - \tan \left( \frac{\pi}{4} \right) \tan \left( \frac{\pi}{6} \right)} \][/tex]

Substitute the values:
[tex]\[ \tan \left( \frac{7 \pi}{12} \right) = \frac{1 + \frac{1}{\sqrt{3}}}{1 - 1 \times \frac{1}{\sqrt{3}}} \][/tex]

Simplify the numerator and the denominator separately:
[tex]\[ \text{Numerator: } 1 + \frac{1}{\sqrt{3}} = \frac{\sqrt{3}}{\sqrt{3}} + \frac{1}{\sqrt{3}} = \frac{\sqrt{3} + 1}{\sqrt{3}} \][/tex]

[tex]\[ \text{Denominator: } 1 - \frac{1}{\sqrt{3}} = \frac{\sqrt{3}}{\sqrt{3}} - \frac{1}{\sqrt{3}} = \frac{\sqrt{3} - 1}{\sqrt{3}} \][/tex]

Combine these results:
[tex]\[ \tan \left( \frac{7 \pi}{12} \right) = \frac{\frac{\sqrt{3} + 1}{\sqrt{3}}}{\frac{\sqrt{3} - 1}{\sqrt{3}}} = \frac{\sqrt{3} + 1}{\sqrt{3} - 1} \][/tex]

At this point, we rationalize the result:
[tex]\[ \tan \left( \frac{7 \pi}{12} \right) = \frac{(\sqrt{3} + 1)(\sqrt{3} + 1)}{(\sqrt{3} - 1)(\sqrt{3} + 1)} = \frac{(\sqrt{3} + 1)^2}{3 - 1} = \frac{3 + 2\sqrt{3} + 1}{2} = \frac{4 + 2\sqrt{3}}{2} = 2 + \sqrt{3} \][/tex]

Numeric evaluation of [tex]\(2 + \sqrt{3}\)[/tex]:
[tex]\[ 2 + \sqrt{3} \approx 3.732050807568876 \][/tex]

Thus, the value of [tex]\(\tan \frac{7 \pi}{12}\)[/tex] is:
[tex]\[ \boxed{3.732050807568876} \][/tex]
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.